Influence of the magnetic field on properties of hot electron emission from ablative plasma produced at laser irradiation of a disc-coil target. (1st November 2022) - Pisarczyk, T; Renner, O; Dudzak, R; Chodukowski, T; Rusiniak, Z; Domanski, J; Badziak, J; Dostal, J; Krupka, M; Singh, S; Klir, D; Ehret, M; et al.
Abstract: Optical generators of strong magnetic fields based on the laser-driven-coil target concept are considered to be useful tools for studies of magnetized plasmas in particular, for the study of implosion of magnetized fusion targets in inertial fusion research and astrophysical applications. This paper presents the results of the research directed at an investigation of the plasma properties in a laser-induced magnetic field. In the experiment carried out on the kilojoule PALS laser facility, a generator of the magnetic field was a disc-coil (DC) target composed of a Cu disk coupled to a single-turn coil irradiated by a 1 ω laser beam with an energy of 500 J. The attention was focused on examining the influence of the magnetic field on properties of the hot electron (HE) flux emitted from the front surface of the irradiated target. The three-frame complex interferometry and four-frame x-ray camera combined with the measurements of the HE population and energy using a multi-channel magnetic electron spectrometer and 2D-resolved imaging of the induced Cu K α line emission were applied to characterize the ablative plasma and the generated particles. Based on the measured angular distributions of the electron energy spectra, 3D simulations have been performed to visualize the effect of the magnetic field on the HE flux and to provide information on space-time distribution of the electron and current density both without and with the presence of an axial magnetic field. The obtained results confirmed the possibility of generating magnetic fields above 5 T using the proposed DC target design as well as the significant impact of these fields on properties of the ablative plasma and the HE emission.